Arquitetura Escolar: um olhar para o ensino de ciências - Deitos, Greyze Maria Palaoro (2017)
ABSTRACT: Architecture at school comes up with a history that has not shown significant changes regarding physical conditions of this environment. It has perpetuated itself over the centuries by showing a remarkable and formal character and establishing stiffness as well as little dynamism on its environments use. It is wellknown the main cognitive activities related to learning are developed within the school environment, so, it is necessary a careful look at the influences that school architecture reflects on teaching/learning process, as human beings who build their scholarship. So, regarding this issue, this research aimedat answeringsome questions about the architectural conditions of the science laboratories in Cascavel municipality, the use frequency of this environment and the conception between Science Teaching and experimentation, which is understood by teachers and municipal coordinators in education. This dissertation reviewed bibliographical, documentary and field research areasin order to bring significant contributions concerning the studied theme. The bibliographic research allowed to know what has been produced on this research theme, consequently becoming a fundamental theoretical reinforcement. Thus, several authors were researched and cited throughout this research. In documentary area, primary documents were analyzed, mainly legislation and regulations that approached the theme about school science laboratory for the initial years of elementary education, in order to make the data more reliable. On the other hand, the field study has understood how the analyzed events are happening day by day at school. So, several questionnaires and photographic records were used in order to elucidate the architectural conditions of the laboratories and Science conceptions, perceived by teachers and school coordinators. The engineer, responsible for the architectural projects of schools, was also interviewed in order to understand the process that they have taken to receive a science laboratory. According to the research data, it was observed that from the 50 schools, only eight of them had a science laboratory, which means a very small number of schools. Five laboratories were visited and a questionnaire was applied. And, it was observed a very limited use of these environments by students and teachers in experimental activities. In addition, only one laboratory showed a considerable level of safety and conditions of use, however, it was inaugurated recently. Two of them are used for other purposes and two others were in very poor maintenance. There is still a misunderstanding conception of Science related when related to experimentation. Most of the questionnaires indicated that the empirical-inductive conception of the experiment still goes through teachers and coordinators’understanding. These results indicate that there is a notorious need for a teacher training that values the Natural Sciences. So, when science is used in experimentation, it has to be really effective in student’s learning. Finally, architecture at school needs to be open to school pedagogical programs in order to provide